THE APPLICATION OF MORAL VALUES IN THE BOOK OF AL AKHLAQ LIL BANAAT AND ITS EFFECT ON CHANGES IN THE BEHAVIOR OF SANTRI AT AL ISLAM DARUL FALAH ISLAMIC BOARDING SCHOOL MASARAN SRAGEN - Widhowati, Anita; Khoir, Mulyanto Abdullah (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This research on the book Al Akhlaqu lil banaat aims to see how much influence it has on the morals of female students at the Al Islam Darul Falah Islamic Boarding School, Sragen. The method used in this study is a qualitative and quantitative method. The results of this study are that the implementation of morality in Islamic boarding schools is carried out in several ways, namely habituation, regulations and threats of sanctions, as well as non-formal regulations in the form of adab towards teachers. Meanwhile, the morals possessed by the female students in all aspects, namely the morals towards Allah, the morals towards teachers and friends, all of them received good ratings. However, there were conflicts and backbiting activities that led to bad judgment. Whereas in the influence of the book Al Akhlaqu lil banaat it shows that activities based on interest in reading books have an influence or found coefficients above 0.3 in all aspects (Akhlaq to Allah, Akhlaq to teachers and Akhlaq to friends). But it lacks a correlation between the value of report cards and the morals of Santriwati, namely the values of the report cards and the morals to God (0.160), the morals to teachers (0.126), and the morals to friends (0.035). This low coefficient indicates a lack of appreciation of values during learning, and the orientation of the female students is only towards the meaning of the reading in the book Al Akhlaqu lil banaat which is in Arabic only.